Synthesis, computational studies, and Hirshfeld surface analysis of 2H-chromen-2-one and imine derivatives - Odame, Felix; Madanhire, Tatenda; Harrison, Jerry Joe Ebo Kingsley; Boadi, Nathaniel Owusu; Hosten, Eric (European Journal of Chemistry, 2023)
Some 2H-chromen-2-one and imine derivatives have been synthesized through a one-pot condensation of aldehydes, diethyl malonate, and amine compounds. The compounds obtained have been characterized using FTIR, NMR, GC-MS, and elemental analysis. The single-crystal X-ray structure of 3-[piperidine-1-carbonyl]-2H-chromen-2-one (2) has been presented. Compound 2, recrystallized in the monoclinic space C2/c (no. 15), a = 16.654(15) Å, b = 8.789(7) Å, c = 18.460(18) Å, β = 102.89(5)°, V = 2634(4) Å3, Z = 8, T = 296(2) K, μ(MoKα) = 0.091 mm-1, Dcalc = 1.298 g/cm3, 17626 reflections measured (4.528° ≤ 2Θ ≤ 57.446°), 3321 unique (Rint = 0.0313, Rsigma = 0.0257) which were used in all calculations. The final R1 was 0.0441 (I > 2σ(I)) and wR2 was 0.1329 (all data). The experimental bond lengths, bond angles, and other topological properties of compound 2 were compared with the DFT calculated results, the comparison showed good agreement with each other with varying level deviations. The energy levels of HOMO and LUMO, as well as the global chemical reactivity descriptors of representative compound 2, have been presented. A discussion of the Hirshfeld surface analysis of compound 2 has been carried out to provide insight into its structural properties.